bentuk sederhana dari
[tex] \frac{ \sqrt{6} }{3 - 2 \sqrt{3} }[/tex]
adalah...
jawab dengan langkah-langkahnya
[tex] \frac{ \sqrt{6} }{3 - 2 \sqrt{3} }[/tex]
adalah...
jawab dengan langkah-langkahnya
Penjelasan dengan langkah-langkah:
[tex] = \frac{ \sqrt{6} }{3 - 2 \sqrt{3} } \times \frac{3 + 2 \sqrt{3} }{3 + 2 \sqrt{3} } [/tex]
[tex] = \frac{3 \sqrt{6} + 2 \sqrt{18} }{9 + 6 \sqrt{3} - 6 \sqrt{3} - 4 \sqrt{9} } [/tex]
[tex] = \frac{3 \sqrt{6} + 2.3 \sqrt{2} }{9 - 4.3} [/tex]
[tex] = \frac{3 \sqrt{6} + 6 \sqrt{2} }{9 - 12} [/tex]
[tex] = \frac{3 \sqrt{6} + 6 \sqrt{2} }{ - 3} [/tex]
[tex] = - \frac{3 \sqrt{6} + 6 \sqrt{2} }{3} [/tex]
[answer.2.content]